Role and contribution of the nurse in caring for patients with palliative care needs: A scoping review. - Sue Moran; Maria E Bailey; Owen Doody (PLoS ONE)
Background The provision of high-quality palliative care is important to nursing practice. However, caring for palliative care patients and their families is challenging within a complex everchanging health environment. Nonetheless the caring, artistic role of the nurse is fundamental to the care of the patient and family. However, this role is currently being overshadowed by the technical and scientific elements of nursing. Methods A scoping review was conducted utilising Arksey and O'Malley's framework to identify the role and contribution of nurses in caring for patients with palliative care needs. An open time period search of eight electronic databases (MEDLINE, CINAHL, Academic Search Complete, PsycINFO, EMBASE, Web of Science, Scopus and Cochrane Library) was conducted on the 8th of March 2023 and updated on the 30th of April 2024. Screening was performed independently by two reviewers against eligibility criteria with meetings between authors to discuss included papers and form a consensus. Data was extracted relating to palliative care nursing, methodology, key findings, and recommendations. The analysed and summarised data was mapped onto Oldland et al seven domains framework: (a) medical/nursing and technical competence, (b) person centred care, (c) positive interpersonal behaviours, (d) clinical leadership and governance, (e) promotion of safety, (f) management of the environment, and (g) evidence-based practice. Results Fifty-five papers met the criteria for this review which describes the role and contribution of nurses in caring for palliative patients across all domains of professional practice. The review found the leading areas of nurse contribution were person centred, interpersonal and nursing care aspects, with leadership, managing the environment, patient safety and evidence-based practice evident but scoring lower. The contribution of the nurse in palliative care supports a biopsychosocial-educational approach to addressing the physical, emotional and social needs of patients with palliative care needs and their families across the care continuum. Conclusion Nurses in palliative care engage in a wide range of roles and responsibilities in caring for patients and their families with palliative care needs. However, there remains minimal evidence on the assessment, intervention, and evaluation strategies used by nurses to highlight the importance of their role in caring for patients and their families in this area. The findings of this review suggest that the artistic element of nursing care is being diluted and further research with a focus on evidencing the professional competence and artistic role of the nurse in the provision of palliative care is required. In addition, research is recommended that will highlight the impact of this care on patient and family care outcomes and experiences.